Forward single‐cell sequencing into clinical application: Understanding of ageing and rejuvenation from clinical observation to single‐cell solution - Furong Yan; Zhangping Li; Charles A. Powell; Xiangdong Wang (Wiley, 2022)
Abstract Ageing is the part of natural biology lifespan and living pathology healthspan that is associated with impact from stress, environmental changes and diseases. The present Editorial emphasises the understanding of ageing biology and potential impact of rejuvenating interventions as a critical focus of clinical and translational medicine. The discovery and development of ageing‐associated biomarkers and therapeutic targets require understanding of the complexity of molecular metabolisms, immune responses and genetic regulations associated with ageing and rejuvenation. Transcriptomic patterns of circulating immune cells, red blood cells and platelets at single‐cell solution can be an important window to molecular mechanisms of ageing initiation and development. As part of programmes, deep understanding of ageing and rejuvenation correlations of clinical with single‐cell transcriptomics will provide more innovative opportunities to translate single‐cell RNA sequencing (scRNA‐seq) to clinical application.